Charge-altering releasable transporters enhance mRNA delivery in vitro and exhibit in vivo tropism - Li, Zhijian; Amaya, Laura; Pi, Ruoxi; Wang, Sean K.; Ranjan, Alok; Waymouth, Robert M.; Blish, Catherine A.; Chang, Howard Y.; Wender, Paul A. (Nature communications, 2023)
The introduction of more effective and selective mRNA delivery systems is required for the advancement of many emerging biomedical technologies including the development of prophylactic and therapeutic vaccines, immunotherapies for cancer and strategies for genome editing. While polymers and oligomers have served as promising mRNA delivery systems, their efficacy in hard-to-transfect cells such as primary T lymphocytes is often limited as is their cell and organ tropism. To address these problems, considerable attention has been placed on structural screening of various lipid and cation components of mRNA delivery systems. Here, we disclose a class of charge-altering releasable transporters (CARTs) that differ from previous CARTs based on their beta-amido carbonate backbone (bAC) and side chain spacing. These bAC-CARTs exhibit enhanced mRNA transfection in primary T lymphocytes in vitro and enhanced protein expression in vivo with highly selective spleen tropism, supporting their broader therapeutic use as effective polyanionic delivery systems. Polymers are promising for mRNA delivery, but can have limited efficacy in hard to transfect cells. Here, the authors report charge-altering releasable transporters for improved mRNA transfection in primary T-lymphocytes and enhanced and selective protein expression in vivo.